Corrosion and tribocorrosion behavior of micro-arc oxidized titanium surfaces functionalized with poly(ethylene glycol) and antimicrobial peptides - Costa, Natália De Araújo Da; Alves, Alexandra C.; Rossi, André Linhares; Ribeiro, Ana R.; Monteiro, Cláudia; Martins, M. Cristina L.; Lisboa Filho, Paulo Noronha (Elsevier, 2026)
This paper investigates the corrosion and tribocorrosion behavior of titanium surfaces treated with micro-arc oxidation (MAO) and further functionalized with poly(ethylene glycol) (PEG) and an antimicrobial peptide (AMP). PEG was first covalently conjugated onto the MAO surfaces followed by AMP physical adsorption. The MAO layer maintained its porosity and bulk chemical composition (Ca+P) after surface functionalization with PEG-AMP. Although no significant differences on the corrosion mechanisms were observed, the corrosion resistance of the MAO surfaces was slightly improved by the presence of PEG-AMP. This corrosion improvement was mainly attributed to the outer porous oxide layer, where PEG-AMP may create a barrier between the MAO layer and the corrosive medium. In addition, although coefficient of friction (COF) has been slightly increased on the PEG-AMP functionalized MAO surfaces, the bulk titanium was effectively protected under loading and reciprocating sliding conditions, which demonstrates a good tribocorrosion behavior.
Corrosion and tribocorrosion behavior of micro-arc oxidized titanium surfaces functionalized with poly(ethylene glycol) and antimicrobial peptides
Keywords: Titanium; Micro-arc oxidation; Surface functionalization; Poly(ethylene glycol); Antimicrobial peptides; (tribo)corrosion